2009
DOI: 10.1177/1079063209353183
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Sexual Perpetration Against Children: Effects of Attachment Style, Interpersonal Involvement, and Hypersexuality

Abstract: This study explores in an adolescent sample hypotheses about child sexual abuse perpetration drawn from contemporary theories that implicate insecure attachment and adolescent social development. Specifically, three 13- to 18-year-old adolescent male samples (sex offenders with child victims, sex offenders with peer/adult victims, and nonsex delinquent youth) were compared in a cross-sectional design. Participants completed a computer-administered self-report questionnaire and a semistructured attachment style… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 55 publications
6
52
3
1
Order By: Relevance
“…In this view, self-control varies across contexts and situations (Tittle, Ward, & Grasmick, 2004;Wikström & Treiber, 2007), and low sexual self-control may contribute to adolescent rape independent of self-control in non-sexual situations. Consistent with this thesis, studies of relatively small samples of juvenile sex offenders in treatment programs, detention centers, and probation departments have reported that adolescent sexual offenders were less able to control sexual urges than non-sexual offenders (Miner et al, 2010) and that sexual compulsivity and preoccupation increased the likelihood of sexual coercion (Knight & Sims-Knight, 2003, 2005.…”
Section: Sexual Psychological and Social Deficitsmentioning
confidence: 76%
See 1 more Smart Citation
“…In this view, self-control varies across contexts and situations (Tittle, Ward, & Grasmick, 2004;Wikström & Treiber, 2007), and low sexual self-control may contribute to adolescent rape independent of self-control in non-sexual situations. Consistent with this thesis, studies of relatively small samples of juvenile sex offenders in treatment programs, detention centers, and probation departments have reported that adolescent sexual offenders were less able to control sexual urges than non-sexual offenders (Miner et al, 2010) and that sexual compulsivity and preoccupation increased the likelihood of sexual coercion (Knight & Sims-Knight, 2003, 2005.…”
Section: Sexual Psychological and Social Deficitsmentioning
confidence: 76%
“…Empirical studies of the effects of sexual promiscuity on juvenile sex offending generally suggest that the number of sexual partners is not directly related to sexually coercive behavior Seto & Lalumière, 2010;Van Wijk et al, 2005). The two studies that contradict this trend (Driemeyer, Spehr, Yoon, Richter-Appelt, & Briken, 2013;Miner et al, 2010) relied on data from small samples of identified sex offenders and measured promiscuity using categorical variables rather than a continuous measure of the number of sexual partners.…”
Section: Sexual Psychological and Social Deficitsmentioning
confidence: 96%
“…The perpetrators are more aggressive and cause more serious physical and emotional damage than female perpetrators (Davies, Pollard, & Archer, 2006). One theory regarding male perpetrators of child sexual abuse is that they might be more able to use their physical strength to control and limit the child victim's resistance, thereby attempting to satisfy their attachment needs and intimacy desires, which fail to be satisfied through normal relationships (Miner et al, 2010). Carlstedt and colleagues (2009) reported that male perpetrators with mental health problems, such as anxiety and depressive symptoms, who manifest aggression and hostility toward women were more likely to abuse young children.…”
Section: Gender Differencesmentioning
confidence: 97%
“…Rejection by peers and lack of intimate relationships could contribute to seeking intimacy and autonomy by abusing even younger children or using their authority to satisfy their sexual desires (Miner et al, 2010). Family characteristics could further influence juvenile offenders.…”
Section: Juvenile Perpetratorsmentioning
confidence: 99%
“…This overview has reported only a minor part of the several hypotheses concerning the etiology of juvenile sex offending, and there would be many other aspects of this topic to analyze, such as the association between adolescent sex offending and autism spectrum disorders symptoms [1], the relationship between sexual offending and sex chromosome abnormality [11], or -from a psychological perspective -the effects of attachment style, interpersonal involvement, and hypersexuality in sexual perpetration against children [12].…”
Section: Part I: Diagnostic and Therapeutic/rehabilitative Strategiesmentioning
confidence: 99%